Strength and competitiveness are more strongly predictive of retrospective sport participation than 2D:4D in university-aged women - Elizabeth T. Vandenborn; Cayla N. Wood; Krista J. Munroe-Chandler; Kevin J. Milne (Canadian Science Publishing, 2019)
Objective: Females continue to participate in sport at lower rates than males. Girls who participate in sport gain many advantages. Even with programs designed to emphasize participation, some females continue with sport participation while others do not. Given the advantages and controversies surrounding testosterone and female sport, it is possible that testosterone may predispose females toward sport participation. Our objective was to determine if the second to fourth digit (2D:4D) ratio, a proxy for prenatal androgen exposure, correlates with sport participation throughout female adolescence and young adulthood. Methods: A cross-sectional analysis of indirect prenatal androgen exposure (i.e., 2D:4D) was completed on 18-30-year-old women (n = 92) using demographics, anthropometrics, sport-specific behaviour tendencies, and retrospective sport participation. Results: 2D:4D was not significantly correlated with total sport participation (TSP) (r = −0.065, p = 0.538). Secondary analyses revealed significant correlations between TSP and maximum hand grip (r = 0.406, p = 0.000) and the Sport Orientation Questionnaire (SOQcomp (r = 0.513475, p = 0.000), SOQgoal (r = 0.253, p = 0.015), SOQwin (r = 0.366, p = 0.000)). Conclusion: Although strength and competitiveness are strongly correlated with female sport participation, the impact of prenatal androgen exposure (i.e., 2D:4D) remains to be determined given its weak and negative association with female sport participation. Given that females participate in sport at lower rates than males, continuing to determine what factors influence sport participation is an important goal.